Projektionsfläche Natur. Zum Zusammenhang von Naturbildern und gesellschaftlichen Verhältnissen - Fischer, Ludwig (Hamburg University Press, 2004)
This volume collects the revised contributions of a conference that took place in March 2002 at the Warburg-Haus in Hamburg. It was organised as part of the "Nature in Conflict" research project, which was funded by the Volkswagen Foundation within the framework of the "Key Humanities Issues" funding programme. This interdisciplinary project was dedicated to the investigation of mental concepts, images, models and value attributions that belong to the collective fund of our ideas of nature. In this context, the investigations are directed from the perspective of various disciplines - ethnology or social anthropology, history, coastal research in the natural sciences, literature, linguistics and media studies - in particular at those images of nature and models that belong to the argumentations and convictions that are often not discussed.